Effect of trap states on photocatalytic properties of boron-doped anatase TiO2 microspheres studied by time-resolved infrared spectroscopy. Issue 8 (6th February 2019) - Du, Yijie; Wang, Zhuan; Chen, Hailong; Wang, Hao-Yi; Liu, Gang; Weng, Yuxiang
Abstract : The photocatalytic hydrogen and oxygen evolution switching effect in the water splitting of two boron-doped anatase TiO2 microspheres was elucidated from the viewpoint of trap states. Abstract : The features of the electronic structure of semiconductor photocatalysts are fundamental to understanding the corresponding photocatalytic process. Besides the bandgap and edges, the behavior of photogenerated charge carriers and trap states can also greatly affect the photocatalytic process but it has been less considered during the material design. A previous study (G. Liu, J. Pan, L. Yin et al., Adv. Funct. Mater., 2012, 22, 3233–3238) showed that the interstitial boron on anatase {001} facets can change the photocatalytic preference from reductive H2 evolution to oxidative O2 evolution in the water splitting reaction, interpreted as the change in the band edges. In this work, we employed transient infrared absorption–excitation energy scanning spectroscopy and femtosecond time-resolved mid-infrared spectroscopy to investigate this phenomenon in view of the effect caused by the boron dopant on the photogenerated carrier kinetics and the energy level distribution of the trap states. We found that the surface boron doping eliminates significantly the trap states above the valence band, which improves its photocatalytic oxygen generation. On the other hand, surface boron doping also introduces a substantial amount of electron recombination centers ( i.e., B σ + in the shell layer). Furthermore, surface boron doping also leads to an inefficient electron transfer from TiO2 to the co-catalyst Pt. Both of these effects give rise to its inferior photocatalytic capability in H2 evolution.